The military and the state in Central Asia : from Red Army to independence - Marat, Erica (Central Asian studies series ;, 2010)
The military played a pivotal role in the political development, state functions, foreign policy and the daily lives of the people in the Central Asian states from the early twentieth century until the present. This book is the first major, in-depth study of the military institutions and the influence they had on the state and society.